2012
DOI: 10.1111/j.1476-5381.2012.01981.x
|View full text |Cite
|
Sign up to set email alerts
|

Pregabalin‐ and topiramate‐mediated regulation of cognitive and motor impulsivity in DBA/2 mice

Abstract: BACKGROUND AND PURPOSEImpulsivity is a core symptom in many neuropsychiatric disorders. The main objective of this study was to evaluate the effects of topiramate and pregabalin on the modulation of different impulsivity dimensions in DBA/2 mice. EXPERIMENTAL APPROACHThe effects of acute and chronic administration of pregabalin (10, 20 and 40 mg·kg -1 ) and topiramate (12.5, 25 and 50 mg·kg -1 ) were evaluated in the light-dark box (LDB), hole board test (HBT) and delayed reinforcement task (DRT). a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 108 publications
(127 reference statements)
1
13
0
Order By: Relevance
“…However, topiramate alone was not able to reduce the response to ethanol. This result agrees with those from previous studies that showed either that topiramate did not alter the responses of mice to ethanol (Navarrete et al ., ), or that topiramate was ineffective in reducing ethanol consumption in Wistar rats (Breslin et al ., ; Lynch et al ., ). However, our results contrast with other reports showing that topiramate reduced ethanol consumption and reduced the motivation to lick for beer in animal models (Hargreaves and McGregor, ; Knapp et al ., ; Nguyen et al ., ), and reduced ethanol consumption, craving and increased the number of abstinent days from ethanol use in humans (Johnson et al ., ; Rubio et al ., ; Shinn and Greenfield, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, topiramate alone was not able to reduce the response to ethanol. This result agrees with those from previous studies that showed either that topiramate did not alter the responses of mice to ethanol (Navarrete et al ., ), or that topiramate was ineffective in reducing ethanol consumption in Wistar rats (Breslin et al ., ; Lynch et al ., ). However, our results contrast with other reports showing that topiramate reduced ethanol consumption and reduced the motivation to lick for beer in animal models (Hargreaves and McGregor, ; Knapp et al ., ; Nguyen et al ., ), and reduced ethanol consumption, craving and increased the number of abstinent days from ethanol use in humans (Johnson et al ., ; Rubio et al ., ; Shinn and Greenfield, ).…”
Section: Discussionmentioning
confidence: 99%
“…We focused on the prefrontal cortex because of its contribution to addictive behaviour (Lüscher and Malenka, ), the involvement in regulating cognitive behaviour in rodents and in humans (Dayas et al ., ; Vengeliene et al ., ; Abernathy et al ., ), and the susceptibility to the effects of topiramate on genetic expression (Navarrete et al ., ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In DBA/2J mice, which show high trait impulsivity, a CB2 agonist decreased impulsive responding and delay discounting, while a CB2 antagonist decreased novelty-seeking behavior and improved prepulse inhibition (PPI) [60]. In another study, the anticonvulsant and mood stabilizer topiramate reduced novelty-seeking behavior, impulsive responding and delay discounting in DBA/2J mice [61].…”
Section: Mouse 'Externalizing' Endophenotypes In Drug Discoverymentioning
confidence: 97%
“…Drugs found to decrease impulsivity and/or delay discounting (externalizing endophenotypes) in the mouse, for example, could be identified as potential pharmacotherapies for human externalizing disorders. An example is topiramate, which has anti-impulsive effects in mice [61], and may be useful to treat several disorders within the 'impulse control spectrum' (e.g., [97]). Given this idea, one would predict that endocannabinoids might be effective for a range of disorders across the internalizing and externalizing dimensions.…”
Section: Expert Opinionmentioning
confidence: 99%